Diagnosis and treatment of neurogenic thoracic outlet syndrome in a collegiate ice hockey player: A case report - Berardo, A.; Friedman, J.; Arlis-Mayor, S.; Diakogeorgiou, E. (International Journal of Athletic Therapy & Training, 2023)
A 22-year-old male ice hockey player reported days of worsening bilateral upper-extremity weakness, hand tremors, and difficulty grasping his stick. Subjective information included sleeping in a "curled-up" position due to lack of heat in their residence. Provocation tests and imagining studies were positive for thoracic outlet syndrome. Primary treatment focused on decreasing stress on the anterior chest wall while secondary treatment focused on strengthening the posterior thorax to improve posture. Emphasis is given to core stability and scapular mobility. Removal from sport never occurred, but symptom alleviation occurred after 3 weeks. Thoracic outlet syndrome can be resolved quickly if proper recognition and adequate treatment are utilized. Athletic trainers fill a sociomedical role for their patients and should perform patient-centered care rather than tunnel vision on the pathology.